Adhesion on different rate of binder and aggregate for chip seal - Khalid, Nor Ikhwan (2010)
Chip seal is a frequently used as preventive maintenance treatment on flexible pavements. The construction of chip seal should be monitored and the technique must be used correctly especially when spreading the binder and the aggregate. The objective of this study is to investigate and to determine the best adhesion of chip seal based on the rate of aggregate and binder. Three different size of aggregate with the different rate are used in this study which are (12, 14, 16 and18 kg/m2) for 14mm size; (8, 10, 11 and 12 kg/m2) for 10mm size and (5, 6 7 and 8 kg/m2) for 6mm size. The penetration grade 80/100 pen bitumen is used as the binder with different rate for every size of aggregate which are (1.50, 1.60 and 1.70 l/m2) for 14mm ; (1.30, 1.40 and 1.50 l/m2) for 10mm and (1.10, 1.20 and 1.30 l/m2) for 6mm aggregate size. Vialit test and pull out test are conducted on every sample to investigate and determine the best adhesion of chip seal. From vialit test result, the percentage of aggregate retained is increases as the binder rate increases. The difference percentage of aggregate retained is around 0% to 0.85%. Besides that, at the same rate of binder shows that percentage of aggregate retained decreases when aggregate rate increases around 1.10% to 2.87%. The combination between smallest aggregate rate and highest binder rate provide the great adhesion between aggregate and binder. The pull out test result shows that highest binder rate gave the highest average maximum load. The highest average maximum load is about 41.970 N for 14 mm, 25.515 N for 10 mm and 15.409 N for 6 mm aggregate size. The best adhesion between aggregate rate and binder rate are (12 kg/m2 and 1.70 l/m2) for 14mm, (8 kg/m2 and 1.50 l/m2) for 10mm and (5 kg/m2 and 1.10 l/m2) for 6mm aggregate size.